Effect of Glycerine Suppository in Achieving Early Full Feeds in Premature Infants: A Randomised Controlled Trial - Ashish Kumar Gupta; Ram Pal Singh Tomar; Sajith Surendra (JCDR Research and Publications Pvt. Ltd., 2019)
Introduction: Achieving full feeds in premature infants is challenging as it can be delayed due to immaturity of their gut. Osmotic agents orally and as suppositories or enemas can be used to stimulate the passage of meconium to promote early feeding but there is little evidence to support this practice as studies have been inconclusive. Aim: To determine the effect of using glycerine suppository in premature neonates on their time required to achieve full feeds in comparison with premature neonates with no glycerine suppository. Materials and Methods: This study was a randomised, double blinded trial conducted on premature infants, with birth weight <1500 g and a gestational age <32 weeks. Study group received 500 mg glycerine suppository twice daily, started within 48 hours of life for 14 days, while Control Group (CG) received no intervention. The results were plotted in MS Excel and analysed using SPSS 22. Results: Total 50 cases, 25 neonates in each group were analysed for the primary and secondary outcomes. Mean duration for full feeds was achieved by 11.1 days in the Glycerine Suppository Group (GSG) and 11.9 days in Control Group (CG) (p-value 0.2). While the duration of hospital stay was shorter in the GSG than the CG (38.4 days vs 40.7 days), but was not statistically significant (p-value 0.49). Conclusion: There was no statistically significant difference seen between the groups in achieving Full Enteral Feeds (FEF). No differences were observed between the groups in regaining birth weight, duration of hospitalisation or incidence of complications including Necrotising Enterocolitis (NEC).